NATUREZA E COLETIVIDADE: O DIREITO NATURAL DE GROTIUS E AS QUESTÕES AMBIENTAIS CONTEMPORÂNEAS - Ferreira de Almeida, Sizinio Lucas (Prometheus - Journal of Philosophy., 2020)
This paper will discuss the approximation of modern natural law in contemporary environmental discussions. To this end, the present text will contain two moments: we will first start from the theory of natural law elaborated by the Dutch philosopher and jurist Hugo Grotius. In his theory, Grotius argues that the seas and waters should be used collectively, as opposed to any monopolistic form. Following this, we will approach the theory of two contemporary authors, Canadian activist Maude Barlow and Indian philosopher Vandana Shiva. In their works, they criticize contemporary privatist intentions, allied to the defense of their collective use, with ethical principles that are close to natural law.